Correlation Between Conventional Theory and Islamic Economic Thought - Novita, Dwi; Asnaini, Asnaini; Putra, Haris Maiza (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This study discusses conventional economic theory, Islamic economic thought, and its correlation or relationship. Conventional economics views worldly life as an absolute right for humans, while Islamic economics teaches that worldly life is based on the principle of accountability to Allah SWT. Because of this difference, location of the difference is presented in this paper. This research is library research, conducted by analyzing and interpreting the theoretical matters related to the research. The results showed that; First, conventional economics is an economic theory related to